Association between Soil Fertility and Growth Performance of Planted Shorea macrophylla (de Vriese) after enrichment Planting at Rehabilitation Sites of Sampadi Forest Reserve, Sarawak, Malaysia - Mugunthan, A/L Perumal; Mohd Effendi, Bin Wasli; Ho, Soo Ying; Jonathan, Lat; Hamsawi, Sani (Hindawi Publishing, 2017)
A study was conducted to determine the status of soil properties after enrichment planting in comparison to an adjacent secondary forest and to evaluate the effect of enrichment planting of Shorea macrophylla (de Vriese) on the soil fertility status with special reference to Soil Fertility Index (SFI) and Soil Evaluation Factor (SEF) at Sampadi Forest Reserve, Sarawak. The study sites were stands rehabilitated in different years (1996: SM96; 1997: SM97; 1998: SM98; 1999: SM99) and secondary forest (SF). Findings indicated that the soils at rehabilitation sites and SF were strongly acidic in nature, with pH less than 5.50, poor soil exchangeable bases, and nutrient status. The soils were relatively of sandy clay loam to sandy clay. Principal Component Analysis revealed the three most significant components of the soil properties which explained 76.3% of the total variation. At surface soils, SFI was correlated with tree growth parameters of S. macrophylla, indicating that SFI is an applicable soil quality index as compared to SEF. Notwithstanding, a significant association was found between soil available phosphorus and planted S. macrophylla, indicating that soil phosphorus is a better indicator than SFI. Further studies on other environmental factors influencing tree growth performance, early establishment of experimental reforestation at nursery, and field should be implemented to obtain the initial data on seedling growth performance prior to outplanting.